Processo de produção e processo de trabalho na cultura do café: uma comparação entre café commodity e café especial do Sul de Minas Gerais. - Sanchez, Alda Maria Napolitano (Universidade Federal de São Carlos, 2007)
The main objective of the present work is to verify life and work conditions of the workers of the commodity coffee cultivation and of the special coffee in the South of Minas Gerais, a region representing approximately 50% of Brazil s coffee production. Coffee cultivation has been considered as one of the most important agricultures since the end of the XVIII century, subsequently Brazil maintains a ranking as the largest coffee producer in the world. Besides financial transactions in coffee agrobusiness, it can be considered that coffee cultivation is among the farming areas that most employs workmanship in agricultural lands, preceded by cereal crops, sugar cane and citrus fruits (orange). Since 2000, coffee cultivation yields have not been favorable to the Brazilian producers, that being the case, a discussion has begun on the need to increase these revenues and on opening consumer markets for Brazilian coffee. With this in mind, a value aggregation pursuit for coffee has become today s focal point. The research carried out in the producing farms addressed the coffee production processes as well as the work process. This investigation enabled to perceive the existing differences in the production processes and also in the work processes amid the farms. By detailing each of the activities and investigating the existing work relationships in the varying coffee productions, it was observed that the special coffee plantations demand a great deal more work to perform their labor in order to assure quality coffee, on the other hand, they improve the worker s life and work conditions, especially in view of the fact that the special coffee producers need to meet the demands of the international market for their coffee to be accepted, and it is through this correlation that the worker is benefited.
Keywords: Café; Café - cultivo; Sistema de produção; Trabalho; Coffee cultivation; Value aggregation; Productive process; Work condition; Special coffee; ENGENHARIAS::ENGENHARIA DE PRODUCAO